Use the quadratic formula to solve for \( x \). \[ 6 x^{2}-6 x-1=0 \] (If there is more than one solution, separate
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To solve the quadratic equation \( 6x^{2} - 6x - 1 = 0 \) using the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \), we first identify the coefficients: \( a = 6, b = -6, c = -1 \). Now we calculate the discriminant: \[ b^2 - 4ac = (-6)^2 - 4(6)(-1) = 36 + 24 = 60. \] Now, applying the values in the quadratic formula: \[ x = \frac{-(-6) \pm \sqrt{60}}{2(6)} = \frac{6 \pm \sqrt{60}}{12}. \] We can simplify \( \sqrt{60} \) as \( \sqrt{4 \cdot 15} = 2\sqrt{15} \): \[ x = \frac{6 \pm 2\sqrt{15}}{12} = \frac{6}{12} \pm \frac{2\sqrt{15}}{12} = \frac{1}{2} \pm \frac{\sqrt{15}}{6}. \] Thus, the solutions are: \[ x = \frac{1}{2} + \frac{\sqrt{15}}{6}, \quad x = \frac{1}{2} - \frac{\sqrt{15}}{6}. \]